Sistem zagotavljanja kakovosti COBIB.SI - Dornik, Ema (Knjižnica, 2017)
Purpose: The activities that are a part of the quality assurance system for bibliographic and authority records within COBISS.SI, carried out by the Institute of Information Science (IZUM), are presented. The activities focus on the quality monitoring of records created by cataloguers - beginners, the identification of groups of bibliographic records with common error patterns, and the quality monitoring of new bibliographic records created daily (group of records created on a certain day). The activities are presented by the analysis of data for the year 2016. Methodology/approach: Different types of sampling bibliographic records and the corresponding authority records were used; the recommendations for the selected records were based on expert review, valid cataloguing rules and COMARC format. The cataloguers were requested to correct the errors manually. Results: The data analysis showed that the activities contributed towards the identification and correction of some of the errors within the bibliographic records. The results showed a good response rate; the cataloguers were informed by e-mail and welcomed the suggestions. Additional help and telephone support were also provided. Research limitation: The paper does not provide a detailed analysis of the recommendations and data quality evaluation of the records; the review was based on data in the records only without the original item in hand. Originality/practical implications: The activities are presented to the professional public for the first time. Some improvements of the cataloguing module are presented as a result of COBIB.SI quality control.
Keywords: COBIB.SI; shared cataloguing; vzajemna katalogizacija; bibliographic records; authority records; bibliografski zapisi; normativni zapisi; quality; kakovost